Binding of CD40L to Mac-1's i-domain involves the EQLKKSKTL motif and mediates leukocyte recruitment and atherosclerosis-but does not affect immunity and thrombosis in mice - Wolf, Dennis (2011)
Rationale: CD40L figures prominently in chronic inflammatory diseases such as atherosclerosis. However, since CD40L potently regulates immune function and hemostasis by interaction with CD40 receptor and the platelet integrin GPIIb/IIIa, its global inhibition compromises host defense and generated thromboembolic complications in clinical trials. We recently reported that CD40L mediates atherogenesis independently of CD40 and proposed Mac-1 as an alternate receptor. Objective: Here, we molecularly characterized the CD40L-Mac-1 interaction and tested whether its selective inhibition by a small peptide modulates inflammation and atherogenesis in vivo. Methods and Results: CD40L concentration-dependently bound to Mac-1 I-domain in solid phase binding assays, and a high-affinity interaction was revealed by surface-plasmon-resonance analysis. We identified the motif EQLKKSKTL, an exposed loop between the α1 helix and the β-sheet B, on Mac-1 as binding site for CD40L. A linear peptide mimicking this sequence, M7, specifically inhibited the interaction of CD40L and Mac-1. A cyclisized version optimized for in vivo use, cM7, decreased peritoneal inflammation and inflammatory cell recruitment in vivo. Finally, LDLr -/- mice treated with intraperitoneal injections of cM7 developed smaller, less inflamed atherosclerotic lesions featuring characteristics of stability. However, cM7 did not interfere with CD40L-CD40 binding in vitro and CD40L-GPIIb/IIIa-mediated thrombus formation in vivo. Conclusions: We present the novel finding that CD40L binds to the EQLKKSKTL motif on Mac-1 mediating leukocyte recruitment and atherogenesis. Specific inhibition of CD40L-Mac-1 binding may represent an attractive anti-inflammatory treatment strategy for atherosclerosis and other inflammatory conditions, potentially avoiding the unwanted immunologic and thrombotic effects of global inhibition of CD40L.